FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGETAHUAN PEKERJA SEKS KOMERSIAL TERHADAP PENULARAN PENYAKIT MENULAR SEKSUAL DI WILAYAH PUSKESMAS II BATURADEN KABUPATEN BANYUMAS TAHUN 2012 - Murniati Murniati; Rosi Kurnia Sugiharti (Viva Medika, 2013)
Sexually transmitted diseases is growing very rapidly-related changes insexual behavior and the proliferation of high-risk behavior groups, such ascommercial sex workers. Based visit STI clinics at the health center II Baturadenmostly suffered is cervicitis, vaginal bacteria, and candidiasis and interview somecommercial sex workers the majority only knows how limiting transmission of STDs.To determine the level of knowledge by age, education level, length of time becomeprostitutes. This research method is quantitative descriptive cross-sectionalapproach, using primary data drawn from the health center II Baturaden andLocalization Gang Sadar. Data collection was done on 27 to 30 June 2012. Analysisof univariate and bivariate analysis with data analysis Chi Square. Number ofsamples 45 respondents. Knowledge of commercial sex workers against transmission of sexuallytransmitted diseases is quite good as much as 44% (N = 20), and unfavorable15.60% (N = 7). Based on the knowledge age is quite good at the age of 20-25 years22.2% (N = 10), and less good at age <20 years of 4.4% (N = 2). Based oneducational level of knowledge is quite good at SMP 20% (N = 9), SMA 20% (N = 9)and lack of knowledge of both SD 6.7% (N = 3). Based on the length becomeprostitutes knowledge of good and pretty well owned the PSK 1-3 years 22.2% (N =10), and less well on the respondent <1 year 11.1% (N = 5). The age and educationlevel affect the level of knowledge of commercial sex workers against transmission ofsexually transmitted diseases in the health centers ii Baturaden Banyumas regency in2012. Key words : sex worker, knowledge of diseases sexual transmission